THE EFFECT OF USING PREVIEW QUESTION READ SUMMARIZE AND TEST (PQRST METHOD) TOWARDS STUDENT’S READING COMPREHENSION AT THE ELEVENTH GRADE STUDENT’S OF SMAN 4 KOTABUMI ACADEMIC YEAR 2018/2019 - Putri Dasena; Asep Hardian; Rini Susilowati (Journal of English Education, Literature and Linguistics, 2019)
This research was conducted because there was an assumption that many students in class XI of SMA 4 Kotabumi had low ability in reading comprehension. The final goal of this research paper is to find out whether there is an effect of using Preview, Question, Read, Summarize, and Test (PQRST) method towards students reading comprehension at the eleventh grade students’ of SMA Negeri 4 Kotabumi Academic year 2018/2019. The method used in this research was quasi experimental design. The population in this research was all students of class XI of SMA Negeri 4 Kotabumi. The sampling technique used was purposive sampling technique. The sample in this research was class XI IPS 1 and XI IPS 4. The experimental class was treated using the PQRST method while the control class was not treated. The instrument used in this research was a multiple choice question test which consisted of 30 items for the pretest and posttest. The research instrument was given before and after the treatment. Meanwhile validity and reliability of the instrument had been calculated before it was tested. Based on the results of the t test by calculating the data obtained from the data post test student test results, then the results obtained tcount = 2.830. By using a significant level of 5% known ttable = 2,0003 so H0 is rejected, it is resulting that Ha accepted. This shows that there is an effect on the application of Preview, Question, Read, Summarize, and Test (PQRST) Method towards student’s reading comprehension at the eleventh grade student’s SMA Negeri 4 Kotabumi Academic Year 2018/2019.